Estimating the population size of lemurs based on their mutualistic food trees. (29th August 2018) - Herrera, James P.; Borgerson, Cortni; Tongasoa, Lydia; Andriamahazoarivosoa, Pascal; Rasolofoniaina, B. J. Rodolph; Rakotondrafarasata, Eli R.; Randrianasolo, J. L. Rado Ravoavy; Johnson, Steig E.; Wright, Patricia C.; Golden, Christopher D.
Abstract: Aim: Species' distributions and abundances are primarily determined by the suitability of environmental conditions, including climate and interactions with sympatric species, but also increasingly by human activities. Modelling tools can help in assessing the extinction risk of affected species. By combining species distribution modelling of abiotic and biotic niches with population size modelling, we estimated the abundance of 19 lemur taxa in three regions, especially focusing on 10 species that are considered Endangered or Critically Endangered. Location: Madagascar. Taxa: Lemurs (Primates) and angiosperm trees. Methods: We used climate data, field samples, and published occurrence data on trees to construct species distribution models (SDM) for lemur food tree species. We then inferred the SDMs for lemurs based on the probability of occurrence of their food trees as well as climate. Finally, we used tree SDMs, topography, distance to the forest edge, and field estimates of lemur population density to predict lemur abundance in general linear models. Results: The SDMs of lemur food trees were stronger predictors of the occurrence of lemurs than climate. The predicted probability of presence of food trees, slope, elevation, and distance from the forest edge were significant correlates of lemur density. We found that sixteen species had minimum estimated abundances greater than 10, 000 individuals over >1, 000km 2 . Three lemur species are especially threatened, with less than 2, 500 individuals predicted for Cheirogaleus sibreei, and heavy hunting pressure for the relatively small populations of Indri indri and Hapalemur occidentalis . Main conclusions: Biotic interactors were important variables in SDMs for lemurs, allowing refined estimates of ranges and abundances. This paper provides an analytical workflow that can be applied to other taxonomic groups to substantiate estimates of species' vulnerability to extinction.